Applications of Oil Palm Ash and Various Types of Organic Fertilizer on Acid Soil (Ultisol) for Onion (Allium ascalonicum L) - Siti Zahrah; Nursamsul Kustiawan (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Onion production in Riau Province is still low, while the demand is quite large. Therefore, it is necessary to increase production. This study aimed to determine the effect of the application of oil palm ash and various types of organic fertilizers on ultisol soils on the growth and production of shallots. The design used was a completely randomized factorial design consisting of 2 factors. The first factor was the provision of oil palm ash which consisted of 4 levels of treatment, namely: 0, 200,400, and 600 g/plot. The second factor is various types of organic fertilizers which consist of 4 levels of treatment, namely: without giving organic fertilizer, chicken manure, tankos compost and corn litter bokashi. The parameters observed were plant height, number of tubers per clump, wet tuber weight per clump, dry tuber weight, percentage of tuber weight loss, relative growth rate and nutrient uptake. plants, number of tubers, wet weight per clump, dry weight per clump and tuber weight loss, the best treatment was giving palm ash 400 g/plot and corn litter bokashi. The main effect of giving palm ash bunches was real on all observation parameters, the best treatment was 400 g/plot. The main effect of organic fertilizer was real on all observed parameters. The best treatment was corn litter bokashi.